The impact of cyclooxygenase inhibitor use on urinary prostaglandin metabolites in preterm infants - Natsuki Ohkawa; Hiromichi Shoji; Naho Ikeda; Yayoi Murano; Toshiaki Okuno; Masato Kantake; Takehiko Yokomizo; Toshiaki Shimizu (Pediatrics and Neonatology)
Background: There is limited evidence on the association between the clinical course of patent ductus arteriosus (PDA) and prostaglandin (PG) metabolites. This study aimed to determine the influence of PDA treatment on urinary PG metabolite excretion in very-low-birth-weight (VLBW) infants. Methods: Urine samples were collected from 25 VLBW infants at 1, 3, and 7 days of age. Infants were separated into two groups: a PDA-treated group that received a cyclooxygenase-2 (COX) inhibitor (n = 12) and a control group that did not receive a COX inhibitor during the first 7 days after birth (n = 13). Urinary PG metabolite tetranor prostaglandin E2 metabolite (t-PGEM) and tetranor prostaglandin D2 metabolite (t-PGDM) levels were analyzed using liquid chromatography–tandem mass spectrometry. Results: Urinary t-PGEM excretion levels were not significantly different between the groups at 1, 3, and 7 days of age. Urinary t-PGDM excretion levels at 1 day of age were higher in PDA-treated infants than in control infants (median [interquartile range]: 5.5 [2.6, 12.2] versus 2.1 [1.0, 3.9] ng/mg creatinine; p = 0.017); however, among PDA-treated infants, the levels were significantly lower at 3 and 7 days than at 1 day of age (5.5 [2.6, 12.2] versus 3.4 [1.7, 4.5] and 4.0 [1.7, 5.3] ng/mg creatinine, respectively; p < 0.05). The urinary t-PGDM excretion level in the control group did not significantly differ among the time points. Conclusion: PDA and COX inhibitor administration affected PG metabolism in VLBW infants. Our results indicated that urinary t-PGDM excretion was significantly associated with PDA-treatment in preterm infants.